Reports, returns and other papers printed by the Houses of Parliament of Great Britain and Ireland [electronic resource] : Behring Sea arbitration, United States case - United States. ([London : Her Majesty's Stationery Office, 1890)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 16007-16012. At head of title: Parliamentary papers. "Volume [4]". Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44